An eco-friendly approach for leather manufacture based on P(POSS-MAA)-aluminum tanning agent combination tannage. (1st June 2020) - Gao, Dangge; Cheng, Yiming; Wang, Pingping; Li, Fan; Wu, Yingke; Lyu, Bin; Ma, Jianzhong; Qin, Jianbin
Abstract: In this work, a novel eco-friendly wet-white tanning approach based on aluminum sulfate and P(POSS-MAA) composite material has been developed to avoid environmental pollution caused by chromium as well as to improve leather performances. shrinkage temperature ( T s ) of combination tanned leather was 73.5 °C higher than aluminum tanned leather, and its whiteness, mechanical properties, thermal stability were obviously higher than those of conventional chrome tanned leather. Scanning electron microscopy (SEM) showed that collagen fibers were dispersed and tanning agents were evenly distributed in collagen fibers. Fourier transform infrared spectroscopy (FT-IR) results revealed that P(POSS-MAA) and aluminum sulfate bonded between collagen bundles and did not enter into the procollagen molecule, destroying the triple helix structure of collagen, which was consistent with X-ray diffraction (XRD), X-ray photo-electron spectroscopy (XPS) and Molecular simulation (MS). Moreover, environmental impact assessment showed that the BOD5 /CODCr of the combination tanning wastewater was more than 0.3, and its biodegradability was superior to that of aluminum tanning and conventional chrome tanning processes. These findings provide a potential application of P(POSS-MAA) to meet related technologies toward eco-friendly leather manufacture. Graphical abstract: Image 1